The effects of metabolic indicators and immune biomarkers on pregnancy outcomes in women with recurrent spontaneous abortion: a retrospective study - Zhang, Jie; Song, Zhan; Yuan, Hui; Cai, Zhu-Hua (Frontiers in Endocrinology, 2024)
The etiology of recurrent spontaneous abortion (RSA) remains elusive despite specific investigations affirming the association between RSA and thyroid autoimmunity (TAI). This study explores the immunological and metabolic profiles of RSA patients exhibiting positive thyroid antibodies and their connection with the rates of first-trimester miscarriage and live births. The aim is to provide further guidance for clinical interventions.Methods: A retrospective analysis included 478 women with RSA. Thyroid profile, thyroid peroxidase antibodies, and anti-thyroglobulin antibodies were measured in all participants. The clinical characteristics and pregnancy outcomes of RSA women were compared between thyroid autoimmunity (TAI)-positive and TAI-negative patients. Significant factors associated with adverse pregnancy outcomes and risk prediction models were explored in TAI-positive patients. Correlation analysis was used to identify specific metabolic or immune biomarkers associated with thyroid autoantibodies.The prevalence of TAI was 18.6%. Compared with women without TAI, the thyroidstimulating hormone (TSH) concentration of TAI-positive RSA was significantly higher (2.80 ± 2.98 vs 1.89 ± 1.17, p=0.006). After 28 weeks, the live birth rate of the TAI-positive group was lower than that of the TAI-negative group, with statistical significance (p<0.05). The immune biomarkers that differed between RSA women with live births and those with first-trimester miscarriages were complement C4 and interleukin-6, respectively, in TAI-negative and TAI-positive women. Then, a risk prediction model for first-trimester miscarriage was constructed for TAI-positive women with an AUC of 0.81. Finally, some factors related to thyroid peroxidase antibody (TPO-Ab) levels were explored, This is a provisional file, not the final typeset article and it was found that TPO-Ab levels were positively correlated with free thyroxine and negatively correlated with 25 hydroxyvitamin D, interleukin-4, and fasting blood glucose in RSA patients.Conclusion: TAI-positive RSA patients have higher first-trimester miscarriage rates and a lower live birth rate, which may be related to metabolic immune shifts in TAI-positive RSA patients.